To lead or to influence? - Do, Victor; Maniate, Jerry M; Sonnenberg, Lyn K (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2021)
One skill set identified within the CanMEDS Framework (CanMEDS) as essential to training future physicians is the Leader role.  Arguably however, the term Leader carries certain connotations that are inconsistent with the abilities outlined by CanMEDS as necessary for physicians.  For example, the term Leader may connote hierarchical authority and formalized responsibilities, while de-emphasizing informal day-to-day influencing.  This CanMEDS role was first labelled Manager, but was re-named Leader in 2015.  Perhaps the focus of this CanMEDS role should be further refined by adopting a more representative term that reflects the concept of intentional influence. Through this lens, learners can discern significant opportunities to influence positively each of the clinical and non-clinical environments they encounter.  We suggest that re-framing the Leader role as an Influencer role will be more comprehensive and inclusive of its full scope and potential.   Accordingly, given the potential for broader applicability and resonance with learners, collaborators, and the populations we serve, consideration should be given to re-characterizing the CanMEDS role of Leader as that of Influencer.